Usborne Adventure Gamebooks - Crofton, Sarah; Knight, Tom (UK, 2023)
Among the shadowy alleys and moonlit rooftops of Morrowstone, a mysterious enemy has kidnapped your friend... And the only person who can rescue him is YOU...In this book of adventure, every choice is yours, and your survival depends on the decisions you make. Who to fight? Who to trust?...
Keywords: Adventure; Juvenile Fiction; Role Playing & Fantasy; Sport and Recreation